2022
DOI: 10.3389/fneur.2022.775190
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effectiveness of Traditional Chinese Medicine Exercise Therapies in Elderly People With Mild Cognitive Impairment: A Systematic Review and Network Meta-Analysis

Abstract: BackgroundMild cognitive impairment (MCI) in the elderly is a health problem worldwide. Studies have confirmed that traditional Chinese medicine (TCM) exercise therapies can improve MCI. However, which therapy is the best and their impacts on brain function remain controversial and uncertain. This study aims to compare and rank TCM exercise therapies for MCI in the elderly, and analyze their effects on brain function, in order to find an optimal intervention and provide a basis for clinical treatments decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…The regimen includes aerobic exercise, resistance exercise, and multiple combination exercises, as well as some traditional Chinese medicine exercises such as Baduanjin. Traditional Chinese medicine exercise therapy has been found to improve cognitive function in elderly patients with mild cognitive impairment (MCI) by regulating cognition-related brain function and structure (Su et al, 2022 ). Although there are many studies on the use of exercise therapy to improve PSCI, there is a relative lack of consensus, and there is no meta-analysis on the effects of exercise therapy on patients with PSCI.…”
Section: Introductionmentioning
confidence: 99%
“…The regimen includes aerobic exercise, resistance exercise, and multiple combination exercises, as well as some traditional Chinese medicine exercises such as Baduanjin. Traditional Chinese medicine exercise therapy has been found to improve cognitive function in elderly patients with mild cognitive impairment (MCI) by regulating cognition-related brain function and structure (Su et al, 2022 ). Although there are many studies on the use of exercise therapy to improve PSCI, there is a relative lack of consensus, and there is no meta-analysis on the effects of exercise therapy on patients with PSCI.…”
Section: Introductionmentioning
confidence: 99%
“…177,[179][180][181][182] Multicomponent intervention studies in rural settings were not found, nor were studies that targeted sleep, yoga, tai chi, or similar mindful movement practices. 183 We encourage researchers to adapt multicomponent interventions for rural populations that are culturally relevant. Evidence for mindfulness-based interventions among older adults with subjective cognitive decline has been mixed, with some studies suggesting no benefit 184 and others suggesting benefits to cognitive function and biomarkers.…”
Section: Mindfulnessmentioning
confidence: 99%
“…Compared with other forms of exercise, TCEs have the advantages of moderate and safe exercise intensity, less stimulation of the cardiovascular system, and no restrictions on the venue. [50] We hypothesized that TCEs could improve vascular function in AD patients. However, the number of relevant studies is currently insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other forms of exercise, TCEs have the advantages of moderate and safe exercise intensity, less stimulation of the cardiovascular system, and no restrictions on the venue. [ 50 ]…”
Section: Introductionmentioning
confidence: 99%